Active methodologies: current trends in mathematics education and its teaching in a Pedagogy course (Research, Society and Development, 2022)
The formal teaching of Mathematics Education in Basic Education begins in Early Childhood Education, then in Elementary School I, and its teaching is the competence of the professional with training in the Degree in Pedagogy: In the initial training, curricular and disciplinary knowledge is ensured in the curricular organization about the teaching contents of Mathematics in this stage of Basic Education. One of the current challenges to improve the teaching and learning of Brazilian students in Mathematics has been the use of various methodological strategies for the teaching of curricular contents, including active methodologies: Tertúlia Pedagogical Dialogic (TDP), with the imbrication of the main national and international trends in Mathematics Education in the teaching-learning process. The methodological path in approaching qualitative research in Action Research procedures, carried out in the second semester of 2019, with 40 students from the Pedagogy course at Ceuenes/Ufes; For data collection, semi-structured interviews and individual textual production were used; For data analysis, the methodology of discursive textual analysis was used. Among the main results, we highlight the contact in the Mathematics laboratory of the 39 students about the main trends in Mathematics Education for teaching the expected contents; Potentiality of the active methodology of the TDP is verified, for the teaching of Mathematics in the Pedagogy course. It is concluded that in the initial training in Pedagogy, ensuring the teaching of the curricular component through the TDP in tessitura with the current trends in Mathematics Education, configures an innovative practice potentiator for the mathematical training of these future professionals in the exercise of teaching in Elementary School I.